A comparative study of the content of some antioxidants in the fruits of autochthonous pomegranate varieties - Selamovska, Ana; Viktor Gjamovski, Milena Taseska-Gjorgjijevski, Dushko Nedelkovski, Klime Beleski, Katerina Bandjo Oreshkovikj, Goran Milanov, Biljana Korunoska (University of Banja Luka, Faculty of Agriculture, 2022)
The contents of total phenolics, anthocyanins, flavan-3-ols, and the fruit antioxidant activity of 9 pomegranate varieties (‘Zumnarija’, ‘Bejnarija’, ‘Valandovska kisela’, ‘Valandovska kiselo-slatka’, ‘Hidjas’, ‘Kisela’, ‘Karamustafa’, ‘Lifanka’, and ‘Ropkavec’) were examined. Autochthonous pomegranate varieties contained 4354.4 – 6480.9 mg/kg FW total phenols, 160 – 698.2 mg/kg FW anthocyanins, 96.9 – 157.2 mg/kg FW flavan-3-ols, and high antioxidant activity of fruits (71.2 – 92.5% inhibition). The ‘Valandovska kisela’ variety had the highest content of total phenolics (6480.87 mg/kg FW), flavan-3-ols (157.190 mg/kg FW) and higher fruit antioxidant activity (92.5% inhibition) compared to the standard ‘Karamustafa’ variety and the other autochthonous varieties. The ‘Hidjas’ variety had the highest content of anthocyanins (698.20 mg/kg FW). A positive correlation (0.9815) was found between the content of total phenolics and the fruit antioxidant activity. A moderate positive, insignificant correlation was also found between the content of flavan-3-ols and anthocyanins. Key words: Autochthonous pomegranate varieties, Total phenolics, Anthocyanins, Flavan-3-ols, Antioxidant activity.
Keywords: Autochthonous pomegranate varieties, Total phenolics, Anthocyanins, Flavan-3-ols, Antioxidant activity